Reversibility of the Ex‐Solution↔Redispersion Processes of Rhodium in Rh0.15Ce0.85O2‐y Nanoparticles Deposited on Functionalized Alumina. Issue 8 (12th May 2020) - Ledwa, Karolina A.; Kępiński, Leszek; Pawlyta, Mirosława
Abstract: Uniform, highly dispersed (<5 nm) Rh0.15 Ce0.85 O2‐y nanoparticles deposited on the alumina support functionalized with alkylsilane were obtained in this work and studied in detail, to characterize their basic properties and thermal stability in the oxidizing and reducing atmosphere. In the next step, the possibility to perform the reversible ex‐solution of Rh nanoparticles in the reducing environment (500 °C, H2 ), and its redispersion into the cerium oxide structure in the oxidizing environment (400 °C, air) was studied with the use of a wide range of experimental methods (XRD, Raman spectroscopy, STEM‐HAADF/EDS, H2 ‐TPR/TPO, XPS). Good reduction‐oxidation reversibility of the metal ions in ceria nanoparticles was proved, with no increase of the nanoparticles' size. In the reducing atmosphere, small particles of reduced rhodium were formed, and these particles disappeared in the oxidizing environment. Also, the number of oxygen vacancies significantly changed depending on the treatment. Abstract : Rhodium‐doped ceria nanoparticles stabilized on the alumina support were analyzed in detail to check for the possibility to perform the reversible ex‐solution and redispersion of rhodium. The system showed very high stability and good reversibility of reduction and oxidation in the successive treatments. It makes this material very promising as a future smart catalyst for the redox reactions.